1998
DOI: 10.1002/(sici)1521-4141(199809)28:09<2619::aid-immu2619>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Anti-IL-4 treatment prevents dermal collagen deposition in the tight-skin mouse model of scleroderma

Abstract: The tight-skin (Tsk/+) mutant mouse, a putative murine model of scleroderma, is characterized primarily by the excessive deposition of collagen and other extracellular matrix molecules in the dermis, and also by a developmentally acquired defect in pulmonary architecture. Passive transfer experiments have suggested an etiologic role for the immune system in Tsk/+ dermal pathology. In addition, CD4+ T lymphocytes have been shown to be required for the excessive accumulation of dermal collagen in these mice. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
80
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(87 citation statements)
references
References 42 publications
4
80
0
3
Order By: Relevance
“…8 The fibrogenic role of IL-4 and IL-13 has been demonstrated with the use of Schistosoma mansoni-induced fibrotic hepatic disease, 8,17 and blocking IL-4 prevented collagen deposition and fibrosis in a mouse model of scleroderma. 18 In vitro studies have further confirmed the stimulatory effects of IL-4 and suppressive effects of IFN-␥ on fibroblast proliferation and collagen deposition. 19,20 It is therefore likely that Th2 cytokines are important for the development of fibrosis in the pericardium in EAM.…”
Section: Discussionmentioning
confidence: 82%
“…8 The fibrogenic role of IL-4 and IL-13 has been demonstrated with the use of Schistosoma mansoni-induced fibrotic hepatic disease, 8,17 and blocking IL-4 prevented collagen deposition and fibrosis in a mouse model of scleroderma. 18 In vitro studies have further confirmed the stimulatory effects of IL-4 and suppressive effects of IFN-␥ on fibroblast proliferation and collagen deposition. 19,20 It is therefore likely that Th2 cytokines are important for the development of fibrosis in the pericardium in EAM.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, the pivotal role of CD4 + T cells in the progression of renal fibrosis was discovered using severe combined immunodeficient mice and a depleting anti-CD4 antibody. 21 Furthermore, numerous studies in cytokinedeficient mice and using neutralizing antibodies have demonstrated that the development of the CD4 + Th2 cell response, including the local production of IL-4 and IL-13, is strongly associated with liver fibrosis, 22,23 scleroderma, 24 and pulmonary fibrosis. [25][26][27] Stimulation of cultured fibroblasts with IL-4 or IL-13 triggers upregulation of the expression of the extracellular matrix proteins type I and III collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Both SSc and cGVHD are characterized by skin, lung, and esophageal involvement and intense fibrosis (1,2). Immunologic similarities include lymphocytic infiltration of affected tissues, the presence of Scl-70 and PM-Scl serum autoantibodies, and up-regulation of a series of cytokines (1,2,(5)(6)(7)(8). Moreover, several reports have indicated that IL-4 production by CD4ϩ T cells infiltrating SSc and cGVHD lesions is prominent in both animal models and humans, suggesting a Th2-polarized phenotype of the specific immune response in both conditions (5)(6)(7)(8)10,11).…”
Section: Discussionmentioning
confidence: 99%
“…The selected CD4ϩ T cell population derived from fetal cell engraftment may be at least partially included in the population of T cells expressing IL-4 that are found in the skin of patients with SSc (5), and it is probably responsible for the enhanced levels of IL-4 in the biologic fluids of these patients (6)(7)(8). Thus, although the results of this study need further investigation, they provide support for the hypothesis that a fetal antimaternal cGVHD may be an immunopathogenic mechanism in the development of SSc in some women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation